Pengaruh Budaya Organisasi terhadap Kinerja Auditor pada Kantor Akuntan Publik di Malang dan Surabaya - Hartidah, Ariyanti Dwi; Ludigdo, Unti (Jurnal Akuntansi Multiparadigma, 2010)
This research is aimed to figure out the effect organization cultures with auditorâs job performance of KAP in Malang and Surabaya. This research uses questionnaire and sampling data uses purposive sampling method. This research also using of 60 from 119 auditors of 5 KAP in Malang and 5 KAP in Surabaya. Data analysis using Multiple Linier Regression with SPSS 15. The result of this research shown Power distance variable (X1), Individualism (X2), Masculinity (X3), and Uncertainty avoidance (X4) are affected simultaneously with Auditorâs job performance (Y), but in partial way only Individualism (X2) which are really affected significantly with Auditorâs job performance (Y), while Power distance variable (X1), Masculinity (X3) and Uncertainty avoidance (X4) are not affectedÂ  significantly.